Method of Construction of Specialized Algorithms for Solving Differential Equations - Verlan, A. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2017)
Considered the problem of optimization of the process of constructing specialized algorithms for the given form nonlinear ordinary differential equations systems’ numerical solution. The problem is reduced to the determination and use of approximating representations of the numerical integration errors by the chosen basic method.